Effect of excessive thickness on microwave absorption performance in SrFe12O19/MWCNT composite materials - Ismail, Ismayadi; Azis, Rabaah Syahidah; Mohd Badrizazli, Puteri Noorzulaikha; Mahmood, Mohd Khairil Adzhar (Springer, 2026)
This research examines the influence of excessive material thickness on the microwave absorption efficiency of SrFe12O19/MWCNT composite materials, emphasizing their electromagnetic properties within the X-band frequency range (8–12 GHz). The synthesis of the composites was performed using high-energy ball milling (HEBM) and chemical vapor deposition (CVD) techniques, followed by comprehensive characterization of their structural, magnetic, and dielectric attributes. The study identified an optimal material thickness of 4 mm, achieving maximum reflection loss (RL) efficiency, with a minimum RL of − 1.16 dB was observed for Sample S3 at a thickness of 6 mm in the X-band (8–12 GHz) in MWCNT-integrated samples. Incremental increases in thickness beyond 4 mm led to reductions in microwave absorption performance, attributed to absorption peak shifts and reduced electromagnetic matching efficiency. Magnetic characterization revealed significant reductions in saturation magnetization (Ms) and retentivity (Mr) in MWCNT-incorporated samples due to structural alterations, while coercivity (Hc) was primarily influenced by grain size and synthesis parameters. Dielectric analysis highlighted the enhancement of dielectric loss (ε″) driven by interfacial polarization and MWCNT distribution, particularly at lower frequencies. These findings show the critical interdependence of material thickness, magnetic, and dielectric properties in optimizing radar-absorbing materials, offering key insights for the advancement of composite nanostructures in electromagnetic wave absorption applications.